2013
DOI: 10.1080/17508975.2013.764838
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of the indoor environment that affect health and wellbeing in healthcare facilities: a review

Abstract: Understanding the physical characteristics of the indoor environment that affect human health and wellbeing is the key requirement underpinning the beneficial design of a healthcare facility (HCF). We reviewed and summarized physical factors of the indoor environment reported to affect human health and wellbeing in HCFs. Altogether, 214 publications were selected for this review. According to the literature, there is strong scientific evidence to show that following indoor environmental factors have beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 151 publications
4
101
0
5
Order By: Relevance
“…Such reviews highlight the lack of an adequate method that integrates credible findings holistically to demonstrate the cumulative and interactive effects of various environmental aspects on occupants' wellbeing. This has been highlighted since 2010 by Durmisevic and Ciftcioglu (2010), Huisman et al (2012), Salonen, Lahtinen, Lappalainen, and Reijula (2013) and Nimlyat and Kandar (2015). However, most of the current research still focuses on examining the effect of a specific HBE characteristic on a specific health outcome for a certain group of occupants.…”
Section: Discussionmentioning
confidence: 99%
“…Such reviews highlight the lack of an adequate method that integrates credible findings holistically to demonstrate the cumulative and interactive effects of various environmental aspects on occupants' wellbeing. This has been highlighted since 2010 by Durmisevic and Ciftcioglu (2010), Huisman et al (2012), Salonen, Lahtinen, Lappalainen, and Reijula (2013) and Nimlyat and Kandar (2015). However, most of the current research still focuses on examining the effect of a specific HBE characteristic on a specific health outcome for a certain group of occupants.…”
Section: Discussionmentioning
confidence: 99%
“…In their report on the Healing Environment within healthcare facilities, the UK's Department of Health concluded that "wounds take longer to heal when patients are exposed to noise for long periods" and "noise can also affect our weight and our hormonal balances" (DoH, 2005). Indeed, it is well known that sound (noise) can significantly disempower individuals and, as a result, have widespread personal and societal consequences (Salonen and Morawska, 2013). As a key contributor to general health problems, it is understood to induce both physiological and psychological harm (Kryter, 1985) and, in so doing, place considerable stress on the core services trying to support those affected.…”
Section: Health and Well-being In The Aural Environmentmentioning
confidence: 99%
“…Further, the incorporation of visual and physical access to nature for hospitalised patients, staff, and visitors results in numerous physiological, psychological, and emotional health benefits. Such benefits include faster recovery, reduced anxiety and pain, lower blood pressure, and less need for pain medication for patients (Ulrich, 2006); reduced stress and anxiety, improved concentration and productivity, and increased job satisfaction for hospital staff (Salonen et al, 2012); and reduced stress and anxiety and improved mood and emotional wellbeing for families and visitors (Salonen et al, 2013).…”
Section: The Theory Of Supportive Designmentioning
confidence: 99%